1983
DOI: 10.1111/j.1365-2125.1983.tb02128.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaco‐EEG profiles of antidepressants. Pharmacodynamic studies with fluvoxamine.

Abstract: 1 Antidepressant drugs produce significant changes in human brain function as reflected in the quantitatively analysed EEG. Two main types of pharmaco-EEG profiles may be differentiated: a thymeretic (desipramine-like) profile characterised mainly by an alpha increase suggesting activating properties and a thymoleptic (imipramine-or amitriptyline-like) profile showing a concomitant increase of slow and fast activities and a decrease in alpha activity indicating also sedative qualities. A small number of compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 13 publications
2
30
0
1
Order By: Relevance
“…This augmentation was more marked after repeated doses (8 to 9% after 10 mg and 9 to 11% after 25 mg) than after an acute dose (4% after 10 mg Time (h) Figure 1 Time course of the EEG changes in the relative beta activity (20- Mean elimination half-life ranged between 7 to 9 h both after a single dose and after repeated administration. AUCs from 0 to 12 h and from 0 to infinity were not (0) [11]. The EEG profile of desipramine 50 mg was similar to that seen after 6 mg methamphetamine 6 mg [11].…”
Section: Eegmentioning
confidence: 68%
See 2 more Smart Citations
“…This augmentation was more marked after repeated doses (8 to 9% after 10 mg and 9 to 11% after 25 mg) than after an acute dose (4% after 10 mg Time (h) Figure 1 Time course of the EEG changes in the relative beta activity (20- Mean elimination half-life ranged between 7 to 9 h both after a single dose and after repeated administration. AUCs from 0 to 12 h and from 0 to infinity were not (0) [11]. The EEG profile of desipramine 50 mg was similar to that seen after 6 mg methamphetamine 6 mg [11].…”
Section: Eegmentioning
confidence: 68%
“…The EEG profile of desipramine 50 mg was similar to that seen after 6 mg methamphetamine 6 mg [11]. A similar profile was seen with antidepressants whose action involves the dopamine (DA) or noradrenaline (NA) systems, such as tranylcypromine, a potent nonreversible MAO-inhibitor, or nomifensine, a DA and NA reuptake inhibitor [8,11].…”
Section: Eegmentioning
confidence: 76%
See 1 more Smart Citation
“…Prior work with "pharmaco-EEG" techniques has shown that the administration of antidepressant compounds yields reproducible changes in EEG activity in healthy control subjects within a few hours of dosing (Saletu et al 1982(Saletu et al , 1983(Saletu et al , 1986(Saletu et al , 1987(Saletu et al , 1987 Grunberger 1985, 1988;Sannita et al 1983;Sannita 1990; …”
Section: Previous Studies Have Shown That Changes In Brain Functionmentioning
confidence: 99%
“…Prior work with "pharmaco-EEG" techniques has shown that the administration of antidepressant compounds yields reproducible changes in EEG activity in healthy control subjects within a few hours of dosing (Saletu et al 1982(Saletu et al , 1983(Saletu et al , 1986(Saletu et al , 1987(Saletu et al , 1987Grunberger 1985, 1988;Sannita et al 1983;Sannita 1990;Itil et al 1984;Herrmann et al 1991;Luthringer et al 1996). The relationship of these immediate EEG changes in control subjects to eventual clinical response in a depressed population is unclear.…”
mentioning
confidence: 99%